Relationship Between Hypertension, Type 2 Diabetes Mellitus, and Cataract with the Incidence of Secondary Glaucoma at the Eye Hospital of West Nusa Tenggara Province - Sulasti Akmaliya; Raden Gunawan Effendi; Ida Ayu Made Mahayani; Herlinawati Herlinawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Glaucoma is a group of optic neuropathies characterized by progressive damage to the optic nerve, often associated with increased intraocular pressure. Secondary glaucoma occurs when elevated intraocular pressure results from other ocular or systemic diseases such as hypertension, diabetes mellitus, or cataract. This study aims to determine the relationship between hypertension, type 2 diabetes mellitus, and cataract with the incidence of secondary glaucoma at the Eye Hospital of West Nusa Tenggara Province. Using a cross-sectional design, this quantitative research involved patient data collected from medical records. Data were analyzed using univariate and bivariate methods with the Chi-square test. The results showed significant associations between hypertension (p-value < 0.05), type 2 diabetes mellitus (p-value < 0.05), and cataract (p-value < 0.05) with the incidence of secondary glaucoma. In conclusion, hypertension, type 2 diabetes mellitus, and cataract are significantly correlated with the occurrence of secondary glaucoma. Further research is recommended to include additional factors such as age, sex, and medication history to better understand the risk factors for secondary glaucoma.